Self-Regulation Based Time Management And Innovative Behavior Among Senior High School Students In Medan City - Babby Hasmayni; Azhar; Ira Dewi; Endang Haryati; Mariah Kibtiyah (Indonesian Journal Publisher, 2026)
This study examined the association between self-regulation–based time management and innovative behavior among senior high school students in Medan City, Indonesia. A quantitative correlational design was applied to a sample of 250 Grade XI students from public and private schools selected using cluster random sampling. Self-report measures assessed self-regulation–based time management (goal setting, planning, self-monitoring, and adaptive adjustment) and innovative behavior in learning contexts (idea generation, idea promotion, and idea implementation). Both instruments demonstrated satisfactory internal consistency (Cronbach’s α = 0.88 and 0.86, respectively). Pearson correlation analysis indicated a moderate positive relationship between self-regulation–based time management and innovative behavior (r = 0.53, p < 0.01). Linear regression analysis further showed that time management significantly predicted innovative behavior, explaining 28% of the variance (R² = 0.28, p < 0.001). These findings indicate that higher levels of self-regulatory time management are associated with greater engagement in innovation-oriented learning behaviors. The results underscore the role of self-regulatory resources in facilitating students’ innovative actions within academic settings. Interventions aimed at strengthening planning, monitoring, and adaptive time management strategies may be effective in promoting innovative behavior among adolescents. Future research should employ longitudinal and multilevel designs to examine causal mechanisms and contextual influences.